Physicochemical, Rheological, and Morphological Characteristics of Products from Traditional and Extrusion Nixtamalization Processes and Their Relation to Starch - Carlos Martín Enríquez-Castro; Patricia Isabel Torres-Chávez; Benjamín Ramírez-Wong; Armando Quintero-Ramos; Ana Irene Ledesma-Osuna; Jaime López-Cervantes; Jesús Enrique Gerardo-Rodríguez (International Journal of Food Science)
The aim of this study was to compare the physicochemical, rheological, and morphological characteristics of corn, nixtamalized flour, masa, and tortillas from the traditional nixtamalization process (TNP) and the extrusion nixtamalization process (ENP) and their relationship with starch. The traditional and extrusion processes were carried out using the same variety of corn. From both processes, samples of ground corn, nixtamalized flour, masa, and tortillas were obtained. The extrusion process produced corn flour with particle sizes smaller (particle size index, PSI = 51) than that of flour produced by the traditional nixtamalization process (PSI = 44). Masa from the TNP showed higher modulus of elasticity (G′) and viscosity (G″) values than that off masa from the ENP. Furthermore, in a temperature sweep test, masa from the TNP showed a peak in G′ and G″, while the masa from the ENP did not display these peaks. The ENP-produced tortillas had higher resistant starch contents and comparable firmness and rollability to those from the TNP but lower quality parameter values. A comparison of the products’ physicochemical properties obtained by the two processes shows the importance of controlling the damage to starch during the milling and extrusion processes to obtain tortillas of better quality. For the first time, we propose the measurement of the viscoelastic parameters G′ and G″ in temperature sweep mode to monitor changes in the degree of starch damage.